Reliving Karbala: Martyrdom in South Asian Memory by Syed Akbar Hyder (New York: Oxford University Press, 2006. 261 pages.) (American Journal of Islam and Society, 2009)
Most studies on the epic events in Karbala and the martyrdom in 680 ofHusayn, the Prophet’s grandson, have focused on the possible ramificationsof his sacrifice and the paradigmatic models that can be constructed fromthis event. Other studies have examined the various genres of Shi`i ritualsenacted to commemorate Husayn’s martyrdom. Akbar Hyder’s RelivingKarbala examines this death from very different perspectives.The author does not claim to provide a systematic exposition of the historicalevents or philosophy of Husayn’s martyrdom. He neither focuses onthe written texts of history nor presents a normative reading of Karbala.Rather, he transcends the traditional Shi`i-coded understanding by offeringa more trans-sectarian and trans-communal, as well as multiple readings, ofthis entire episode. The book also covers Karbala’s influence on the SouthAsian cultural and literary landscape, demonstrating, in the process, how thisnarrative is appropriated and lived in the contexts and memories of SouthAsian Muslims and non-Muslims at different times.Hyder uses a wide array of sources, ranging from classical Islamic textsto modern twentieth-century discourses and incorporates citations from Iqbal, Premchand, Gandhi, and others. The book opens a window on how variousinterpretive strategies can be utilized to read a seventh-century event and howthey can shape social milieus inhabited by more than a billion people ...